Chemistry and Technology of Honey Production - Baglio, Ettore (Chemistry of Foods,, 2018)
This Brief explains and discusses honey and its production from a chemical perspective. It outlines why honey is a special and unique food, being produced by bees from the nectar of plants or from secretions of living parts of plants. Although glucose and fructose are the main constituents of honey, its overall composition is far from being simple or uniform: other substances such as organic acids, enzymes, or minerals are found in varying amounts. In this Brief, the author addresses the factors that influence the composition of the honey as well as the consequences that the composition has on properties such as color, crystallization, density, viscosity, or the refractive index. This Brief also introduces some of the most commonly used quality parameters for the determination of ageing and/or overheating: 5-hydroxymethylfurfural (HMF) and diastase. Other recently proposed constituents for quality parameters are also mentioned, e.g. 1,2 dicarbonyl compounds (3 deoxyglucosone, methylglyoxal, glyoxal) and furosine, also named 2-furoylmethyl lysine.